Acute shallowing of the anterior chamber. Issue 7 (July 1981) - Mapstone, R
Abstract : In aging eyes phenylephrine drops have no significant effect on the depth of the anterior chamber, whereas pilocarpine drops produce a significant shallowing. If both drugs are instilled simultaneously, a significantly greater decrease in anterior chamber depth occurs. The effect is seen in normal, glaucomatous, and hypertensive eyes, and in eyes with shallow anterior chambers. It did not occur in eyes that had had an iridectomy. During the course of a positive provocative test an acute reduction in anterior depth occurs which is reversed when the angle opens and pressure returns to normal levels. It is concluded that the depth of the anterior chamber is not a static dimension but that changes can occur which are rapid and transient. The mechanism of shallowing and deepening depends on an increase or a decrease in the pupil block force. It is a necessary consequence too that eyes with nonshallow anterior chambers can get closed-angle glaucoma and that this possibility cannot be detected by a conventional gonioscopic approach.